2021
DOI: 10.1136/bmjopen-2020-045389
|View full text |Cite
|
Sign up to set email alerts
|

Peer mentorship to improve self-management of hip and knee osteoarthritis: a randomised feasibility trial

Abstract: ObjectiveTo determine the feasibility of conducting a randomised controlled trial (RCT) of a peer mentorship intervention to improve self-management of osteoarthritis (OA).DesignSix-month parallel group non-blinded randomised feasibility trial.SettingOne secondary care and one primary care UK National Health Service Trust.ParticipantsFifty adults aged ≥55 years old with hip and/or knee OA.InterventionsParticipants were allocated 1:1 to the intervention or control group using an online randomisation service. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 56 publications
(52 reference statements)
0
21
0
Order By: Relevance
“…Volunteers were given an educational resource manual and handouts to use in support sessions with mentees. Additional information about peer mentor training and associated costs can be found in the feasibility trial paper [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Volunteers were given an educational resource manual and handouts to use in support sessions with mentees. Additional information about peer mentor training and associated costs can be found in the feasibility trial paper [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The overall aim of the study was to develop and trial a peer mentorship support intervention to improve self-management amongst older people with hip/knee osteoarthritis, and determine the feasibility of conducting a definitive randomised controlled trial (RCT). Using the Medical Research Council guidance on developing and evaluating complex interventions [ 41 ] as a theoretical structure we developed, piloted and evaluated the peer mentorship support intervention as a two-arm randomised feasibility trial, reported elsewhere [ 42 ], with a nested qualitative evaluation, reported here. Key objectives were to assess feasibility and acceptability of the intervention and trial procedures, including: mentor and mentee recruitment and retention; mentor training; intervention costs; completion rates; and potential impacts of the intervention on participants.…”
Section: Study Design Aims and Objectivesmentioning
confidence: 99%
“…Few studies have investigated the relationship between self-efficacy, social support, and self-management in patients with KOA, which are limited to exploring the effect of self-efficacy on self-management of pain control and physical activity [22][23][24], as well as peer support for self-management behaviors [25]. Therefore, underlying mechanisms for associations between social support, self-efficacy and overall self-management behaviors remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 8 9 13 A recent feasibility RCT of peer mentorship for people with osteoarthritis in the UK reports a mixed picture with challenges in matching coaches to peers and difficulties with coach retention alongside positive reports of coach enjoyment and satisfaction. 7 16 We have not located any studies of peer coaching that have targeted peer coaching interventions at patients reporting low levels of activation. People with low levels of activation stand to benefit most from an intervention designed to improve confidence, problem solving and ability to manage their healthcare and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach to staff delivery of coaching services is to involve patients with lived experience as coaches (peer coaches) especially if they are highly activated (PAM levels 3 and 4). There is an expanding body of research exploring the effectiveness of peer coaching provided via a range of delivery modes; in-person7 8; telephone9 10 and digital 11. Recent randomised controlled trials (RCTs) of peer coaching have included people with diabetes9 12 13 and chronic pain 8 14 15.…”
Section: Introductionmentioning
confidence: 99%